1992
DOI: 10.1080/10408347308003991
|View full text |Cite
|
Sign up to set email alerts
|

The effect of promotion on career path choice amongst secondary school pupils

Abstract: The choice of career path facing school-leavers is discussed, using a modified consumer choice model. As a case study, students from 12 high schools in Perth, Australia were surveyed to ascertain their perceptions of the armed services as a career path. The effects of external promotion and family involvement are considered. Major factors that emerged from the study were the difficulty students faced in selecting a career and the importance placed on training offered by the organisation.In recent years the fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Problemsolving stimulates the personal development by a need of knowledge and competence. Concerning the competence in this type of business, the study illuminates that both pipefitting and industrial work presupposes successive learning (compare to Frost, 1992). The informants have good experience from workplaces and education offered by the companies, both internal and external courses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Problemsolving stimulates the personal development by a need of knowledge and competence. Concerning the competence in this type of business, the study illuminates that both pipefitting and industrial work presupposes successive learning (compare to Frost, 1992). The informants have good experience from workplaces and education offered by the companies, both internal and external courses.…”
Section: Discussionmentioning
confidence: 99%
“…This study does not investigate what the youth"s concerned think in the question about future careers, but both teachers in the study say that their students do not have any idea of what they want to do in the future. They begin their training without a clue of what they have embarked on, which can be compared to four of the informants in the present study and also to Frost (1992) who found that career choices often are delayed until late in the school programme. Frost (ibid.)…”
Section: Discussionmentioning
confidence: 99%